Different Models of Wind Speed Prediction; A Comprehensive Review - Lawan, S. M.; Abidin, W. A. W. Z.; Chai, W.Y; Baharun, A.; Masri, T. (International Journal of Scientific & Engineering Research, 2014)
The energy crisis witnessed in the early seventies is a serious problem that had happened in the universe. Hence, induction of renewable energy into electrical power generation mix can serve as an alternative source to cater for the limited reserve of fossil fuels. Wind energy is promising and has emerged as one of the safest, cleanest and fastest growing renewable energy in the recent years. The bottleneck of this type of emission free energy is the variability, stochastic, unpredictable and complex nature of the wind speed. To harness the energy content in a wind efficiently, it’s of utmost importance to accurately predict wind speed and energy with minimum accepted errors for security and economics of wind power utilization. For this reason, it becomes necessary to appraise different types of models used in the wind energy forecast. This paper present review of available wind speeds and power prediction models and discuss their applications and current developments. Moreover, the survey also highlights an overview strength and weakness of these models.